Protecting Japanese giant salamanders (Andrias japonicus) in the Nawa River Basin, Japan: policy recommendations addressing water pollution and waterway disruption - Borzée, Amaël; Angulo, Ariadne; Meredith, Helen; Taguchi, Yuki; Groffen, Jordy; Kohler, Dallin Bradshaw; Abernethy, John Peter Duncan; Othman, Siti N.; Messenger, Kevin; Heo, Kyongman; Wan, Le; Um, Tae Eun; et al. (Frontiers in Amphibian and Reptile Science, 2024)
The Japanese giant salamander, Andrias japonicus, is an iconic but declining species of aquatic amphibian. A population within the Nawa River Basin of Tottori Prefecture persists but faces two significant threats. The first major threat is waterway obstructions, in the form of dams, weirs, and concrete embankments, which severely fragment and degrade the habitat. The second is water pollution, primarily caused by runoff from animal farms. Both threats to A. japonicus can be mitigated with proper actions. We provide science-based recommendations, advocating for the modification of dams and weirs by implementing ladderways to restore habitat connectivity and the provisioning of adequate breeding habitat in the form of artificial nest boxes. We also recommend the implementation of regular water quality monitoring and the enforcement of regulations regarding allowed runoff from animal farms. The Nawa River Basin could also be designated as an official sanctuary area for the Japanese Giant Salamander, lending additional formal protection and providing ecotourism opportunities for economically declining rural areas. Though the threats to A. japonicus are serious, the implementation of these mitigation measures and continual monitoring can allow this remarkable species to thrive.